The Influence Of Leadership Style And Creativity On The Morale Of PT. Rahmat Anugerah Mandiri - Rasid, Muhammad Al Faqri; Munizu, Musran; Wahda, Wahda (Pascasarjana STIE Amkop Makassar, 2024)
The purpose of this is to analyze and test the influence of leadership style and creativity on the morale of PT. Grace Anugrah Mandiri both partially and simultaneously.This research is a research using a quantitative approach. The size of the sample size in this study is 30 respondents which is part of the large population, so the determination of the sample uses simple rendom sampling. The data collection technique used is through the distribution of questionnaires from primary data and secondary data. The analysis method used is multiple linear regression analysis, while for hypothesis testing, t test and F test are used. Kata Kunci: Leadership style, creativity, employee morale